A New Cascode Low Noise Amplifier (LNA) with Double Feedback Technique Architecture for Long Term Evolution (LTE) Application - Abu Bakar Ibrahim; Nurul Husna Kahar; Hafizul Fahri Hanafi; Ashardi Abas; Shamsul Arrieya Ariffin (Journal of Advanced Research in Applied Mechanics, 2021)
The paper aims at designing a new cascode low noise amplifier (LNA) by using double feedback technique architecture for long term evolution (LTE). The objectives of this article is to display the improvement performance of gain with minimizing noise figure with innovative technique for realization of Long Term Evolution (LTE). The innovation technique with implementation double feedback technique architecture outline the possibility to improve the performance in various parameters such as bandwidth, stability, gain, noise figure, power consumption and complexity. The realization using cascode LNA is verify by using FHX76LP Super Low Noise HEMT that operate at 5.8 GHz in compliant with LTE standard. The Advance Design System (ADS) software is used to obtain characteristics for collecting data in smith chart and s-parameter generated by simulation. The cascode LNA with double feedback technique achieve average gain (S_21) of 20.887 dB with noise figure of 0.341 dB. The input return loss (S_11) and output return loss (S_22) are – 14.354 dB and – 11.879 dB respectively. The outcome of this work will contribute in providing a better wireless signal receiver especially for the LTE standard and it potentially in addressing wireless communication issues in rural area.